Isolation and characterization of ethylene receptor genes in dendrobium pompadour - Zuliana, R.; Chandran, S.; Le, A.L.; Boyce, A.N.; Nair, H. (Malaysian Society for Molecular Biology and Biotechnology, 2010)
The generally long life span, unique appearance and attractive colours have transformed orchids from being an exquisite plant enjoyed only by collectors to a plant found in almost every household, airport, hotel and restaurant. However, wounding, pollination and exposure to exogenous ethylene or cigarette smoke may reduce the shelf-life of some orchid species rendering them unmarketable. Therefore, there is a crucial need to circumvent this problem to ensure better quality and commercial value for the sustainability of the orchid industry and competition in the world market. The advent of biotechnology has allowed for genetic engineering of senescence controlling genes in flowers like carnations, resulting in extended shelf-life. The success of this genetic approach is a stepping-stone in the development of transgenic orchids and needs to be buttressed by a strong understanding of the ethylene-related genes involved in senescence. In this paper, we report the cloning and characterization of four known ethylene receptors, ETR1, ETR2, ERS1 and ERS2 from the popular tropical orchid genus Dendrobium, as part of initial steps towards using these genes (sequences) to regulate ethylene sensitivity for greater longevity of pollinated orchid flowers. Physiological studies have shown that within 24 hours, pollinated Dendrobium flowers display an increase in ethylene production, alongside distinct visual changes. The presence of these genes in pollinated and unpollinated flowers was detected using RT-PCR. Detailed analysis, with Scan Prosite, showed that the RT-PCR product of ETR1 shares more than 60 nucleotide sequence homology with the orchid, Phalaenopsis as well as tobacco, rice, petunia and carnation ERS 1 primers produced a product with more than 80 homology with delphinium, as well as a petunia hybrid and Oncidium Gower Ramsey. Sequence results for ETR2 and ERS2 as analysed and characterized using bioinformatics tools will also be presented.